Graphical Models for Security Third International Workshop, GraMSec 2016, Lisbon, Portugal, June 27, 2016, Revised Selected Papers - Kordy, Barbara; Ekstedt, Mathias; Kim, Dong Seong (Security and Cryptology, 2016)
This book constitutes the refereed proceedings from the Third International Workshop on Graphical Models for Security, GraMSec 2016, held in Lisbon, Portugal, in June 2016. The 9 papers presented in this volume were carefully reviewed and selected from 23 submissions. The volume also contains the invited talk by Xinming Ou. GraMSec contributes to the development of well-founded graphical security models, efficient algorithms for their analysis, as well as methodologies for their practical usage. .